Kinetic Study of limonene and glucose adsorption on immobilization and coimmobilization beads - Astrilia - Damayanti; Sarto - Sarto; Wahyudi Budi Sediawan (Dept. of Chemical Engineering, Diponegoro University, 2018)
Rotten oranges contain glucose and limonene, in which limonene is an inhibitor of microorganisms. Immobilization of mixed culture used the entrapment method is the easiest method of protecting the mixed culture from inhibitors. Entrapment method with extrusion drip is an efficient and effective technique to produce beads. This study aims to determine the adsorption rate of adsorbate (glucose and limonene) on the adsorbent surface (beads). Materials used in this study were glucose, DL-limonene, mixed culture, and beads. Three types of beads consisted of alginate - no mixed culture (A), alginate and activated carbon - no mixed culture (CA), alginate and activated carbon - free mixed culture (CB). Adsorption column consist of 30 ml nutrient, 15 mL substrate, and 5 mL beads. If the beads do not contain mixed culture, nutrients and substrate were replaced by aquadest. The reactor was done in a batch system at 37oC. The lowest order of beads ability to adsorb glucose were AG followed by CAG and finally CBG, whereas to limonene solution were AL followed by CBL and finally CAL. Lagergren model was used to determined kinetic bioadsorption on limonene and glucose. The adsorption rate value in the pseudo-second order (k2,ad) for the glucose solution was ranged between 0.025 to 0.087 min-1, while the D-limonene was in the range between 2.084 to 5.233 min-1. Adsorption of glucose and limonene on the surface of the three types of adsorbents was reached steady state at the 60th minute.Keywords: orange, limonene, immobilization, adsorption, Lagergren model.